Pengembangan Kawasan Wisata Bahari Tanjung Kelayang Dengan Pendekatan Recreational Opportunity Spectrum - Budi Wahyuni, Retno (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2019)
ROS is a framework for identifying places of interest. In ROS there are three criteria that are the parameters of experience, environment, location and examples of activities. The measurements of the ROS parameters yield 5 classes ranging from Easily Accessible to Remote Area. . The problem found was tourism marine activities from diving, snorkeling and intentional fishing affecting the quality and the ecosystem existence. This study will review the recreational zone which is not contrary to the principles of marine area management. It is expected that the identification of zoning in the form of marine tourism spectrum classes beside tourism activitie plan using parameters in ROS will make the ​​Tanjung Kelayang area becoming a tourist area not only attracts tourists but also becoming more sustainable. This research uses a descriptive method with qualitative approach (1) describes the potential of Tanjung Kelayang marine tourism area based on Main Attraction, Depth and Air, Latitude and Access. Then after that (2) an analysis with ROS resulted in the classification of ROS Tanjung Kelayang class. Next (3) The ROS classification results will be drawn in the form of GIS with the help of Arc application. GIS and Arc. Map. Based on the results of the study, it was found that Tanjung Kelayang area was included in class 1 or was easily accessible, quite affordable and comfortable, and the quality of DTW was comfortable and well